AN ANALYSIS ON INDONESIAN ELT TEXTBOOK FOR GRADE XI FROM THE PERSPECTIVE OF SLA PRINCIPLES USING LITTLEJOHN’S FRAMEWORK - Christina Atika Yulina (Universitas Suryakancana, 2021)
This paper outlines a procedure for language textbook analysis from the perspective of second language acquisition (SLA) principles using a minimally modified version of Littlejohn’s three-level framework by Guilloteaux as a preliminary procedure to textbook evaluation for selection. The aim is to analyze to what extent does Indonesian ELT textbook for grade XI reflects the universal SLA principles. The universal SLA principles used as material analysis criteria in this paper were drawn from the literature selected by Guilloteaux. This analysis revealed that the Indonesian ELT textbook by the Ministry of Education and Culture reflected SLA principles closely. Although only in-use evaluation can determine the extent to which this textbook actually supports language acquisition, the evidence suggests that the textbook is potentially supportive to English language learning.